Security control of Boolean control networks against periodic DoS attacks - Bowen Bai; Jinhuan Wang; Linying Xiang (Franklin Open, 2025)
This paper studies the stabilization of Boolean control networks (BCNs) under periodic denial-of-service (PDoS) attacks for the first time. DoS attack is one typical form of network attacks that blocks the delivery of information between network nodes. We consider the BCNs under PDoS attacks. Firstly, the control Lyapunov function (CLF) for the BCNs under PDoS attacks is defined, and it is shown that the BCNs can achieve global stabilization if and only if there exists a CLF. Secondly, to decrease the complexity of finding the CLF, we propose a Lyapunov coefficient method to construct the CLF more conveniently. After that, for two cases that the state-control channel and the output-control channel are attacked, we design the corresponding state feedback control and output feedback control, respectively, to stabilize the system globally. Lastly, a numerical example is provided to illustrate the feasibility of the theoretical results.